Indigenous Youths' Experiences at the Undergraduate Program in Indigenous Education, Mexico. Professionalization and Identity. - Santana Colin, Yasmani (2017)
This paper aims to contribute, on the one hand, to the discussion of the homogeneous image that is constructed regarding who we are,  indigenous students; and on the other, to the knowledge of the challenges that we, indigenous youth, face in academic programs. I present the formative experiences of young men and women from different indigenous groups who attended the Indigenous Education Program at the National Pedagogical University - Ajusco Unit in Mexico city. I use interviews with graduates from the 2007-2011 cohort -of which I was part- to discuss what it means to be an indigenous student at the university, what their main problems and expectations are through their training, how they are seen in their communities of origin after becoming professionals, and if their access to the university caused loss of cultural identity. Methodologically, this research was carried out in the frame of collaborative work or dialogical research. Being part of this generation helped me to have the dialogues addressing the issues mentioned above.